Relative Efficacy of Different Insecticides Againsts Chilli Pod Borer, Spodoptera Litura Fabr. (Lepidoptera - Noctuidae) in Manipur - B. Prasad, M. Kumar*, M. Chinamen, Ok. Monorama and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The bio-efficacy of seven insecticides namely Endosulfan (0.07%), Monocrotophos (0.05%), Malathion (0.05%), Dimethoate (0.04%), Phosalone (0.04%), Cypermethrine (0.01%) and Neem oil (3.5%) were applied on Chili. Capsicum annum was grown in the field for the control of Chilli pod borer, Spodoptera litura Fabr. The insecticide like Phosalone (0.04%) and Endosulfan (0.07%) were most effective and the neem oil were found to be the least effective in reducing borer population. Â 